2022
DOI: 10.1002/etc.5296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Separate and Combined Exposure of Cadmium and Lead on the Endochondral Ossification in Bufo gargarizans

Abstract: Cadmium (Cd) and lead (Pb) are ubiquitous in aquatic environments and most studies have examined the potential effects of Cd or Pb alone on aquatic organisms. In the present study, chronic effects of Cd and Pb, alone and in combination, on Bufo gargarizans were investigated by exposing embryos to these contaminants throughout metamorphosis. Significant reductions in body mass and snout-to-vent length were observed in B. gargarizans at Gosner stage 42 (Gs 42) and Gs 46 exposed to a Cd/Pb mixture. Single and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 127 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…Cadmium (Cd) is a widespread environmental pollutant that accumulates in the human body and poses a significant global health hazard. It has been associated with various adverse health effects, such as autoimmune diseases, cancers, cardiovascular diseases, and hepatic dysfunction, with the kidneys being the main targets 1,2 . Studies have shown that Cd can bind to the metal transporter (MT) to form a Cd‐MT complex, which is then transported to endosomes and lysosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium (Cd) is a widespread environmental pollutant that accumulates in the human body and poses a significant global health hazard. It has been associated with various adverse health effects, such as autoimmune diseases, cancers, cardiovascular diseases, and hepatic dysfunction, with the kidneys being the main targets 1,2 . Studies have shown that Cd can bind to the metal transporter (MT) to form a Cd‐MT complex, which is then transported to endosomes and lysosomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been associated with various adverse health effects, such as autoimmune diseases, cancers, cardiovascular diseases, and hepatic dysfunction, with the kidneys being the main targets. 1,2 Studies have shown that Cd can bind to the metal transporter (MT) to form a Cd-MT complex, which is then transported to endosomes and lysosomes. Inside these compartments, Cd 2+ is released from MT and delivered into the cytoplasm through the divalent metal transporter 1 (DMT1), which represents a major way for Cd to enter and accumulate in proximal tubular cells.…”
mentioning
confidence: 99%